Effects of dissimilatory sulfate reduction on Fe-III (hydr)oxide reduction and microbial community development - Kwon, Man Jae; Boyanov, Maxim I.; Antonopoulos, Dionysios A.; Brulc, Jennifer M.; Johnston, Eric R.; Skinner, Kelly A.; Kemner, Kenneth M.; O'Loughlin, Edward J. (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Although dissimilatory iron and sulfate reduction (DIR and DSR) profoundly affect the biogeochemical cycling of C, Fe, and S in subsurface systems, the dynamics of DIR and DSR in the presence of both Fe-III (hydr)oxides and sulfate have not been well-studied with mixed microbial populations. This study examined the response of native microbial communities in subsurface sediment from the U.S. Department of Energy's Integrated Field Research Challenge site in Rifle, CO to the availability of sulfate and specific Fe-III (hydr)oxide minerals in experimental systems containing lactate as the electron donor, with ferrihydrite, goethite, or lepidocrocite and high (10.2 mM) or low (0.2 mM) sulfate as electron acceptors. We observed rapid fermentation of lactate to acetate and propionate. Fe-III reduction was slow and limited in the presence of low-sulfate, but the extent of Fe-III reduction increased more than 10 times with high-sulfate amendments. Furthermore, the extent of Fe-III reduction was higher in ferrihydrite or lepidocrocite incubations than in goethite incubations. Propionate produced during fermentation of lactate was used as the electron donor for DSR. The concurrence of sulfate reduction and Fe-II production suggests that Fe-II production was driven primarily by reduction of Fe-III by biogenic sulfide. X-ray absorption fine-structure analysis confirmed the formation of ferrous sulfide and the presence of O-coordinated ferrous species. 16S rRNA-based microbial community analysis revealed the development of distinct communities with different Fe-III (hydr)oxides. These results highlight the highly coupled nature of C, Fe, and S biogeochemical cycles during DIR and DSR and provide new insight into the effects of electron donor utilization, sulfate concentration, and the presence of specific Fe-III (hydr)oxide phases on microbial community development. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: GREEN RUST FORMATION; NOV SP-NOV; REDUCING BACTERIA; GEN-NOV; MARINE SEDIMENT; FATTY-ACIDS; SUBSURFACE SEDIMENTS; ANAEROBIC BACTERIUM; CHEMICAL-REDUCTION; SURFACE-CHEMISTRY